Analysis of Carbapenemase-Resistant Genotypes of Highly Virulent Klebsiella pneumoniae and Clinical Infection Characteristics of Different MLST Types. (30th September 2021) - Liu, Shuli; Wang, Xiaobo; Ge, Jingjing; Wu, XiangBing; Zhao, Qiu; Li, Yue Man; Wang, Renshu
Abstract : Carbapenemase-resistant Klebsiella pneumoniae (CR-KP) has become one of the nosocomial infections that seriously threaten the lives of patients, greatly increasing the burden on patients. In order to explore the resistance mechanism of clinically isolated CR-KP to carbapenems and perform multilocus sequence typing (MLST), to study the clinical characteristics of patients with different ST types of infection, we collected 74 CR-KP strains clinically isolated from the main 6 hospitals in Zhejiang province from January 2018 to July 2020. The sensitivity of the tested strains to 23 antibacterial drugs was determined by the microbroth dilution method, and PCR was applied. Gene amplification technology and DNA sequencing methods were used to detect the carbapenemase gene of the tested strains. Through the MLST of the tested strains, the clonal correlation and molecular epidemiological characteristics of the tested strains were explored, and the characteristics of CR-KP resistance, resistance mechanisms, and clinical characteristics of bacterial infections under different MLST types were analyzed at the same time. The results showed that 74 carbapenem-resistant Klebsiella pneumoniae strains showed high resistance to 21 commonly used antibacterial drugs, and all carbapenemase phenotypic screening tests were positive. MLST typing showed that 74 CR-KP strains had 17 ST typings, and ST11 was the dominant type (54.05%). The study also found that these ST11 strains are more likely to be resistant to carbapenem antibiotics. Most of them produce KPC carbapenemase, and a few are IMP, VIM, and NDM. Univariate analysis suggested that the proportion of patients in the ST11 group receiving treatment in ICU, the use rate of mechanical ventilation, and the proportion of drainage tube indwelling were higher than those in the non-ST11 group, and the survival rate of the ST11 group was lower than that of the non-ST11 group. Clinical data suggested that the same hospital was dominated by the same clonal epidemic in the same period. In view of the analysis of clinical data suggesting that patients who have received ICU treatment, mechanical ventilation, and drainage tube indwelling are prone to the risk of CR-KP strain (especially ST11) infection and low survival rate, such patients should arouse extensive clinical attention.